Lesson study as a way of reconstructing practical knowledge for improved teaching practice. Seven case studies. - Peña-Trapero, Noemí; Vasquez Suárez, Kena; Rodríguez Rivera, José Antonio; Becerra Mena, Ana Fátima; García de Paz, Sergio (My University, 2015)
With the aim of helping to enrich teacher training processes, using an approach based on Practical Knowledge and Practical Thinking (Schön's knowledge-in-action), the present paper strives to explore and understand the relationships between espoused theories and theories-in-use (action theories by Argyris) of a group of seven pre-school teachers involved in a process of in-service training based on Lesson Study, a powerful methodological tool to identify, contrast and review such theories both autonomously and cooperatively. The conclusion reached is that this training strategy is a rich proposal for the questioning of teaching theory and practice, and, in consequence, for the reconstruction of more unconscious Practical Knowledge, albeit with some circumstantial and personal nuances.
Keywords: Estudio - Métodos; Practical knowledge; Lesson Study; Theories of action; Reflective practice; In-service training